The violent legacy of fascism: Neofascist political violence in Italy, 1969-88 - Stefano Costalli; Daniele Guariso; Patricia Justino; Andrea Ruggeri (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
We still have limited knowledge about the long-term effects of fascism on European democracies. European countries experienced cycles of violence between the 1960s and 1980s. Can such violence be explained by legacies of mobilization during fascism? We study whether and how the Italian fascist experience of the 1920s affected political violence during the 1970s and 1980s. We created an original dataset of conflictual events at a subnational level in Italy. Using zero-inflated negative binomial regressions, we find that local membership of the fascist party in 1922-before the institutionalization of the fascist regime-predicts neofascist political violence at the provincial level more than 40 years later. New windows of opportunity facilitate the resurfacing of local fascist legacies: in the months when a new Minister of Interior is appointed, we observe higher levels of neofascist violence in provinces where the early presence of the fascist party was stronger.
Keywords: 330; conflict; fascism; Italy; legacies; terrorism; violence